Cultural Adaptation by Bangladeshi Migrant Workers in Sarawak, Malaysia: An Empirical Study - Md Mizanur Rahman; Mohamad Taha Arif; Razitasham Safii; Zainab Tambi; Cliffton Akoi; Zulkifli Jantan; Syahrizal Abdul Halim; Ahmad Hafiz (Universitas Muhammadiyah Sidoarjo, 2019)
Cultural adaptation occurs in a wide range of socio-cultural contexts which describe the acquisition of skills and knowledge. The aim of the study was to assess the process of cultural adaptation by the Bangladeshi workers in Sarawak and to compare it with their own culture. This was a cross-sectional study conducted among the Bangladeshi migrant workers in the selected districts in Sarawak. A total of 314 Bangladeshi workers were successfully interviewed using structured questionnaire. Data were collected by face-to-face interview. Data analysis was done by IBM SPSS version 22.0. Data analysis was done in three domains of cultural adaptation which was language adaptation, cultural behaviour and cultural knowledge using 22 items of question. Analysis revealed that language adaptation was quick and sustained which accounted for 53%, while, gaining cultural knowledge was 24% and cultural behaviour was 21%. Overall, 34% adapt local culture of the country of destination and 67% practiced their own culture and the difference was statistically significant (p<0.05). A multiple linear regression analysis revealed that nature of job, income, mode of payment, marital status and health insurance appeared to be important motivating factors for cultural adaptation in Malaysia (p<0.05). The findings suggest that Bangladeshi migrant workers are integrating into Malaysian society, keeping uphold their own culture. Though this study did not depict the overall scenarios, a cross-cultural issues with a rigorous working framework are warranted to get more in-depth cultural adaptation and process among the migrant workers in the country of destination.